Focused Ultrasound for the Treatment of Circuit and Molecular Pathology in Parkinson's Disease - Hahn Kofoed, Rikke; Schwartz Hvingelby, Victor; Pineda-Pardo, Jose A.; Blesa, Javier; Paschen, Steffen; Tandon, Anurag; Joutsa, Juho; Nørgaard Glud, Andreas (John Wiley & Sons, 2026)
Focused ultrasound is rapidly emerging as a novel technology for the development of symptomatic therapies and supporting disease-modifying treatments for Parkinson's disease (PD). At the forefront of this development is thermoablation using high-intensity focused ultrasound, an incisionless treatment that has been extensively tested in clinical trials and so far has received clinical approval for the treatment of essential tremor and PD patients. At the other end of the spectrum, low-intensity focused ultrasound has been demonstrated in both neuromodulation and blood–brain barrier opening to allow the entry of therapeutic molecules into the central nervous system. The aim of this review is both to provide an overview of the current and future roles of focused ultrasound in disease-modifying treatments for PD with a special focus on outlining the full complexity of the disease beyond dopaminergic cell loss and to bridge clinical and preclinical research. First, we establish PD as a disease including both circuit dysfunctions and molecular pathology. Second, we discuss focused ultrasound state-of-the-art clinically and when relevant in relation to other similar treatment strategies (ie, deep brain stimulation). Third, we highlight preclinical advances and the potential of focused ultrasound to become a disease-modifying treatment. Understanding the therapeutic effects of focused ultrasound in a complex disease like PD is necessary to harness the full potential of the technology. © 2026 The Author(s). Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.